3D high-quality temperature-field reconstruction method in furnace based on acoustic tomography. (October 2020) - Kong, Qian; Jiang, Genshan; Liu, Yuechao; Sun, Jianhao
Highlights: A 3D high-quality temperature field reconstruction method is proposed based on acoustic tomography. The proposed method can reconstruct the temperature field with high accuracy, good anti-noise ability and fast convergence rate. Simulations and experimental study are implemented to evaluate the effectiveness of the proposed reconstruction method. Abstract: Reconstructed 3D high-quality temperature distribution in furnace can provide important information to better control boiler operations and to optimize the combustion process. Acoustic travel-time tomography is considered to be a promising method that uses the dependence of sound speed on temperature to reconstruct the temperature field. In this paper, a new 3D temperature field reconstruction method based on radial basis function approximation with polynomial reproduction (RBF-PR) and truncated generalized singular value decomposition (TGSVD) is proposed to solve the inverse problem. To improve the reconstruction quality, we consider the refraction effect of sound waves in the non-uniform temperature field and estimate the sound wave propagation path model in the reconstruction method. The shooting method with improved Powell algorithms is used to solve the propagation path model and obtain the relationship between the acoustic travel-time over the propagation path and temperature distribution. Simulations are implemented to evaluate the effectiveness of the proposed reconstruction method. The results indicate that compared with other methods, the new reconstruction method that considers the refraction effect can reconstruct temperature distribution with higher accuracy and better anti-noise ability. Experimental results also demonstrate that the temperature distribution can be reconstructed effectively by the proposed method.